The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00213-009-1712-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of atypical antipsychotics improves behavioral and synaptic defects of STOP null mice

Abstract: All together, the pharmacological reactivity of STOP null mice to antipsychotics evokes the pharmacological response of humans to such drugs. Totally, our study suggests that STOP null mice may provide a useful preclinical model to evaluate pharmacological properties of antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 47 publications
3
49
1
Order By: Relevance
“…In STOP null mice, mesolimbic dopaminergic hyperactivity is accompanied by reduced glutamatergic transmission (Brenner et al, 2007), an interrelationship now thought to be a neurochemical hallmark of schizophrenia (Carlsson et al, 2000;Jablensky, 2004). Delotterie et al, (2010) reported that long-term treatment with risperidone, a representative atypical antipsychotic drug, did not improve working memory of STOP null mice assessed with the Y maze. This finding is consistent with the lack or weak effects of antipsychotic drugs on cognitive deficits associated with schizophrenia (Young et al, 2009) suggesting that the STOP null mouse may be a useful model for the identification of therapeutics capable of improving the cognition of schizophrenics.…”
Section: Introductionmentioning
confidence: 98%
“…In STOP null mice, mesolimbic dopaminergic hyperactivity is accompanied by reduced glutamatergic transmission (Brenner et al, 2007), an interrelationship now thought to be a neurochemical hallmark of schizophrenia (Carlsson et al, 2000;Jablensky, 2004). Delotterie et al, (2010) reported that long-term treatment with risperidone, a representative atypical antipsychotic drug, did not improve working memory of STOP null mice assessed with the Y maze. This finding is consistent with the lack or weak effects of antipsychotic drugs on cognitive deficits associated with schizophrenia (Young et al, 2009) suggesting that the STOP null mouse may be a useful model for the identification of therapeutics capable of improving the cognition of schizophrenics.…”
Section: Introductionmentioning
confidence: 98%
“…Next steps could include (1) generating (or further characterizing) a preclinical model that mirrors these findings; can an animal that goes through development with an NMDA receptor signaling complex deficit be rescued? (Delotterie et al, 2010;Nagai et al, 2011), (2) further elucidating the contribution of genetic risk factors on PSD95 biology, and/or (3) developing pharmacological interventions that are targeted not at the underlying genetic risk factors (such as DISC1 in subjects with the DISC1 translocation) but instead at common pathophysiological factors such as impaired NMDA receptor signaling.…”
Section: A Mechanism For Nmda Receptor Dysfunction In Schizophreniamentioning
confidence: 99%
“…Deletion of the CB 2 r gene induced depressive-like responses in the tail suspension test. Similarly, Homer1-KO mice and STOP-null mice show increased depressive-like behavior in the Porsolt test (Delotterie et al, 2010;Szumlinski et al, 2005). However, other animal models based on schizophrenia susceptibility gene mutations showed an antidepressant-like response (Barbier and Wang, 2009;Perona et al, 2008;Sakae et al, 2008;Tanda et al, 2009;Yamasaki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%